Resolution of the Portunus gladiator species complex: Taxonomic status and identity of monomia gladiator (fabricius, 1798) and monomia haanii (stimpson, 1858) (brachyura, decapoda, portunidae) - Windsor, A.M. (Pensoft Publishers, 2021)
10.3897/zookeys.858.33826